Neurofilaments as biomarkers in neurological disorders - Khalil, Michael; Teunissen, Charlotte E; Otto, Markus; Piehl, Fredrik; Sormani, Maria Pia; Gattringer, Thomas; Barro, Christian; Kappos, Ludwig; Comabella, Manuel; Fazekas, Franz; Petzold, Axel; Blennow, Kaj; et al. (Nature reviews. Neurology, 2018)
Neuroaxonal damage is the pathological substrate of permanent disability in various neurological disorders. Reliable quantification and longitudinal follow-up of such damage are important for assessing disease activity, monitoring treatment responses, facilitating treatment development and determining prognosis. The neurofilament proteins have promise in this context because their levels rise upon neuroaxonal damage not only in the cerebrospinal fluid (CSF) but also in blood, and they indicate neuroaxonal injury independent of causal pathways. First-generation (immunoblot) and second-generation (enzyme-linked immunosorbent assay) neurofilament assays had limited sensitivity. Third-generation (electrochemiluminescence) and particularly fourth-generation (single-molecule array) assays enable the reliable measurement of neurofilaments throughout the range of concentrations found in blood samples. This technological advancement has paved the way to investigate neurofilaments in a range of neurological disorders. Here, we review what is known about the structure and function of neurofilaments, discuss analytical aspects and knowledge of age-dependent normal ranges of neurofilaments and provide a comprehensive overview of studies on neurofilament light chain as a marker of axonal injury in different neurological disorders, including multiple sclerosis, neurodegenerative dementia, stroke, traumatic brain injury, amyotrophic lateral sclerosis and Parkinson disease. We also consider work needed to explore the value of this axonal damage marker in managing neurological diseases in daily practice.